PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 5 KECAMATAN RUPAT UTAR - Rian Sulisanti; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is conducted because the study result of Social Subjectof the third grade student in SDN 5 Tanjung Punak is low, the Minimum MasteryCriteria decided by school is 70. Among 20 student, there are only 11 Studens (55,00%)who reach the Minimum Mastery Criteria, meanwhile there are 9 students (45,00%)who do not reach the Minimum Mastery Criteria yet. In order to solve this problem,research applied the Snowball Throwing Type of cooperative learning model. The aimof this research is to increase Social Subject Study result of third Grade Studen in SDN5 Tanjung Punak Rupat Utara District by implementing Snwball Throwing Type ofCooperative learning model. Based on the result of researcher data analysis, it isknown that the mean of basic score which is 66,85 increased on the first cycle to 76,75.On the second cycle, the mean score also increased to 92,50. On the basic score, theclassical mastery of students’ study result is 55% (unmaster). After the implementationof Snowball Throwing Type f Cooperative learning model on the first cycle, thestudents’ classical mastery increased to 75% and on the second cycle increased to100%. The percentage of teacher’s activity on the first meeting of first cycle is 54,16%with enough category. On the second meeting increased to 62,50% with good category.On the first meeting of second cycle, the teacher’s activity increased to 75% with goodcategory. On the second meeting increased to 87,50% with very good category. Thepercentage of students’ activity on the first meeting of first cycle is 45,83% with lesscategory. On the second meeting increased to 58,33% with enough category. Then, onthe first meeting of second cycle, the stdents’ activity reincreased to 70,83% whith goodcategory, and on the second meeting increased to 87,50% with very good category. Theincreasement of teacher and students’ activity is also followed by the increasement ofstudents’ mean score, from basic score 66,85% to the end of second cycle to be 92,50%.The increasement of study result is 38,36%. Based on this research, it can be concludedthat implementing snowball throwing type of cooperativelearnimg model can increasesocial subject study result of third grade students in SDN 5 tanjung punak.Keywords : Snowball type of cooperative